Dental and anesthetic management of a child with epidermolysis bullosa - V Rathna Prabhu; P Rekka; Ramesh; S Swathi (Wolters Kluwer Medknow Publications, 2011)
Epidermolysis bullosa (EB) is a wide spectrum of rare genetic disorders characterized by marked fragility of the skin and mucous membranes in which vesculobullous lesions occur in response to trauma, heat, or no apparent cause. This case report deals with the dental and anesthetic management of a 10-year-old girl with dystrophic EB.